O fenômeno da ambiguidade lexical: uma análise do uso de termos ambíguos e os problemas causados por suas ocorrências em relatórios técnicos das ciências contábeis - Garcia, Elias (2016)
The phenomenon of lexical ambiguity vehemently troubles researchers in the area of linguistics, especially in the teaching and learning processes, but not much discussed in the business area. Therefore, this was the focus we chose to study in this thesis. Bring this subject to business. We have noticed that in the accounting activity, the mandatory financial reports issued by professionals carry a high burden of ambiguity, mainly due to polysemy and homonymy. Starting from these findings, the research questions are: i) Is there external interference in the accounting lexicon that defines a terminology of the area? ii) How to reduce the lexical ambiguity present in the accounting reports? In order to answer these questions, we have chosen to study some financial reports that are required by companies, especially public companies, to reflect on the occurrence of the phenomenon of lexical ambiguity in the financial reports of companies. With this objective, we can know the linguistic impacts that this phenomenon can cause in the process of understanding the information disclosed by the accountants in these reports. In order to comply with this objective, we have selected two mandatory reports called "Explanatory Notes to the Financial Statements and Management Report", published by publicly traded companies, Petrobras, Vale, Editora Abril, Bradesco, Banco do Brasil and Embraer (representing all industries, services and commerce). To detect the phenomenon of ambiguity, we studied four terms, CASH, COST, EXPENSE and PROFIT that are frequent in business activity. We use as theoretical support Corpus Linguistics and the Terminology of specialties. The methodology used is based on documentary research with content analysis. After the theoretical discussions on linguistics, corpus linguistics and terminology, we analyzed the existence of ambiguity in the words selected in the reports and explained the possible meanings in each sentence of the selected reports aiming at disambiguation, in order to alleviate the often pernicious effects of the phenomenon for users of the accounting information. As results, we confirm that there is ambiguity in the lexicon of accounting; that there is great external interference of the legislative aspect in the formation of accounting terminology and that much of the accounting information is affected by the phenomenon of ambiguity.